Toxic epidermal necrolysis induced by sintilimab in a patient with advanced non-small cell lung cancer and comorbid pulmonary tuberculosis: A case report - Li, Gang; Gong, Sheng; Wang, Ning; Yao, Xiaojun (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors (ICIs) have had a revolutionary effect on the treatment of patients with advanced non-small cell lung cancer (NSCLC), especially squamous cell lung cancer. However, ICIs may cause associated immune-related adverse events (ir-AEs). No case of sintilimab-induced toxic epidermal necrolysis (TEN) has been reported. In this report, we discussed a patient with advanced NSCLC and comorbid pulmonary tuberculosis who underwent immunotherapy and chemotherapy as neoadjuvant therapy and anti-tuberculosis therapy concurrently. Partial response (PR) of the tumor was achieved after three cycles of neoadjuvant therapy without cutaneous toxicities. Video-assisted thoracoscopic surgery (VATS) left lower lobectomy was performed successfully. Sintilimab and chemotherapy were administered as adjuvant therapy, after which the patient suffered severe TEN that rapidly progressed to cover >50% of the skin. TEN was associated with extensive rashes of the trunk and pruritus. With history of sintilimab use, clinical symptoms, and physical examination, TEN was diagnosed. Intravenous methylprednisolone and oral prednisone were administered until the patient totally recovered from the cutaneous toxicities caused by sintilimab. Monitoring of such rare but severe cutaneous toxicities is essential in patients who are treated with sintilimab.